Meme Marketing: How Do Memes Influence Customer Perception and Awareness of The Brand - Dharmawan, Raden Mas Rizky Benny; Linando, Jaya Addin (Universitas Batanghari Jambi, 2025)
This study aims to explore the responses of Generation Z working in the creative industry to meme-based marketing, identify factors influencing their engagement, and analyze strategies that can optimize meme content to increase brand awareness. This study used a qualitative research design with a phenomenological approach. Data were collected through semi-structured interviews with eight Gen Z professionals in creative fields such as content creation, social media, and digital marketing. The study concluded that Generation Z exhibits a positive attitude toward meme marketing, especially when the content is humorous, relevant, and emotionally authentic. Memes that resemble casual peer communication are more effective in attracting attention and avoiding rejection of promotional messages. This study identified five main factors influencing Gen Z engagement with meme content: humor, emotional connection, trend awareness, simplicity, and authenticity.